Neurociencias a la prueba de la clínica y de las ciencias sociales - Émilie Bovet; Cynthia Kraus; Francesco Panese; Vincent Pidoux; Nicholas Stücklin (Revue d'anthropologie des connaissances)
The scientific, historical, political, cultural and media development of neuroscience is remarkable. Promoted to overcome brain diseases, they promise to answer the old questions of the relationship between thought, body and brain in a definitive way thanks to new techniques of observation. The thematic dossier mobilizes historians, psychiatrists, anthropologists, psychologists, sociologists, neuroscientists and philosophers to shed light on how neurosciences are reconfiguring care practices and to question their ambitions. The contributions testify to the development of critical analyses of the neurosciences and the epistemic and political tensions they maintain with other disciplines. A first set of texts deals with brain imaging devices, the inflation of objects produced and their shaping of the human being. The second set deals with attempts to understand the cerebral bases of mental pathology and the instruments, substances and methods aimed at modifying mental states. It also deals with the transformation of the role of experts and clinical research with evidence-based medicine. The third set raises the question of the articulation between modes of knowledge production, including analysis inherited from feminist studies, denaturalizing the brain to re-politicize gender differences. The articles question the development of neuroscience and its epistemic and practical effects on the human and social sciences, as well as the dynamics of compatibility and tension between different analyses.